Preliminary characterisation of titanium nitride thin film at 300 mK for the development of kinetic inductance travelling wave parametric amplifiers - Longden, J; Boussaha, F; Chaumont, C; Ratter, K; Tan, B (Society of Photo-optical Instrumentation Engineers, 2021)
Travelling wave parametric amplifiers (TWPAs) made from highly nonlinear reactive superconducting thin films have been demonstrated to be a viable technology for various quantum applications, including fundamental physics experiments such as astronomy and axion dark matter searches, as well as commercial applications like quantum computational and communication systems. In this paper, we present the design of a kinetic inductance TWPA comprising a patterned titanium nitride film that can operate at 0.3 K to demonstrate the feasibility of operation closer to 1 K temperature, paving the way to achieve even higher bath temperature operation. We discuss in detail the design of our TWPA, along with the predicted gain-bandwidth product and other characteristics. We perform the preliminary experimental investigation of the thin film properties and compare that with the simulated results. We found that there are several discrepancies between the measured and the predicted behaviour of the thin film. We attribute these differences to the fact that the fabricated thin film has a different gap voltage, resistivity and thickness to what we expected. With a new set of estimated parameters, we successfully reproduce the measured transmission profile. We further show that by utilising bridges to ensure equipotential grounds for the CPW lines, we managed to reduce the rippling effect and achieve higher gain with broader bandwidth. We expect that our TWPA can achieve higher than 20 dB gain from approximately 0–8 GHz.